Evaluation of Renal Perfusion in Hyperthyroid Cats before and after Radioiodine Treatment. (14th October 2017) - Stock, E.; Daminet, S.; Paepe, D.; Buresova, E.; Vandermeulen, E.; Smets, P.; Duchateau, L.; Saunders, J.H.; Vanderperren, K.
Abstract : Background: Hyperthyroidism and chronic kidney disease (CKD) are common in elderly cats. Consequently, both diseases often occur concurrently. Furthermore, renal function is affected by thyroid status. Because changes in renal perfusion play an important role in functional renal changes in hyperthyroid cats, investigation of renal perfusion may provide novel insights. Objectives: To evaluate renal perfusion in hyperthyroid cats with contrast‐enhanced ultrasound (CEUS). Animals: A total of 42 hyperthyroid cats was included and evaluated before and 1 month after radioiodine treatment. Methods: Prospective intrasubject clinical trial of contrast‐enhanced ultrasound using a commercial contrast agent (SonoVue) to evaluate renal perfusion. Time‐intensity curves were created, and perfusion parameters were calculated by off‐line software. A linear mixed model was used to examine differences between pre‐ and post‐treatment perfusion parameters. Results: An increase in several time‐related perfusion parameters was observed after radioiodine treatment, indicating a decreased blood velocity upon resolution of the hyperthyroid state. Furthermore, a small post‐treatment decrease in peak enhancement was present in the renal medulla, suggesting a lower medullary blood volume. Conclusions and Clinical Importance: Contrast‐enhanced ultrasound indicated a higher cortical and medullary blood velocity and higher medullary blood volume in hyperthyroid cats before radioactive treatment in comparison with 1‐month post‐treatment control.